Tectonic Characteristics and its Effect on Shale Gas Preservation Condition in the Jingmen Region - Li, Xiaoming; Wang, Yarong; Lin, Wen; Ma, Lihong; Liu, Dexun; Zhang, Yu (Frontiers in Earth Science, 2022)
Jingmen block is an essential location for the development and exploration of shale gas. The regional structure, the tectonic characteristics, and their influence on shale gas preservation in the Jingmen block were summarized based on observations from drilled cores, seismic data interpretation, FMI imaging logging results, and other methods of subsequent analysis. The study results show that: 1) the overall structure of the study area is simple. The shale corresponding to the Wufeng and Longmaxi formations of the Upper Ordovician and Lower Silurian periods were subjected to compression deformation in Indosinian and early Yanshanianand, following extension and strike-slip transformation in the late Yanshanian period. Structures, including back-thrust, echelon, parallel, inversion structures, and rifts, could also be observed 2) Fractures with different tectonic stages and scales have different effects on the preservation degree of shale gas in the study area, resulting in differences in the nature, scale and zone of influence of faults in different regions and 3) The crack associated with fault structure include interlayer low-angle detachment fracture, conjugate shear fracture, reticular fracture, high-angle shear fracture, high-angle strike-slip shear fracture, and high-angle fracture zone. The location and type of fracture development in different stages vary, which affect the shale gas preservation and migration 4) Based on the influence of structures on shale gas preservation, the study area is divided into four categories viz. two favorable areas and two more favorable areas.